The collagenase of the bacterium Clostridium histolyticum for the treatment of capsular fibrosis after silicone implants - Fischer, Sebastian; Kremer, Thomas; Hirche, Christoph; Kneser, Ulrich (Plastic and reconstructive surgery, 2015)
Background: The main part of the fibrotic capsule in capsular contracture is collagen. The collagenase of the bacterium Clostridium histolyticum is U.S. Food and Drug Administration approved for the treatment of Dupuytren contracture and might be capable of dissolving the fibrotic capsule surrounding silicone implants. Methods: One hundred twenty days after insertion of miniature silicone implants the authors performed in vitro studies (n = 14) for optimum dosage-finding and subsequent in vivo studies (n = 36) to evaluate application method and efficiency. Data analysis involved histologic measurements of capsule thickness and collagen density; 7-T magnetic resonance imaging-based in vivo imaging; and polymerase chain reaction analysis of inflammatory, profibrotic, and antifibrotic markers. Results: Compared with the control group, each dosage showed significantly thinner capsules after in vitro incubation. Skin digestion occurred in 0, 1 (7 percent), and 11 cases (80 percent) after incubation with 0.3, 0.9, and 1.8 mg/ml, respectively. In vivo application showed a dosage-dependent decrease in capsule formation, which was more prominent in lower capsule parts, seen by magnetic resonance imaging. In vivo skin perforation was seen in two (17 percent) and six cases (50 percent) after injection of 0.3 mg/ml and 0.9 mg/ml, respectively. Profibrotic and inflammatory markers were significantly up-regulated 10 days after collagenase injection. Conclusions: The collagenase of C. histolyticum is capable of dissolving the fibrotic capsule surrounding silicone implants. Skin perforation occurred most likely because of mechanical irritation after complete digestion of the capsule. Further studies are required to pave the way for safe clinical application.
Gesehen am 03.08.2021